The cause of the artifact in 4-slice helical computed tomography - Taguchi, Katsuyuki; Aradate, Hiroshi; Saito, Yasuo; Zmora, Ilan; Han, Kyung S.; Silver, Michael D. (Medical physics (Lancaster), 2004)
The causes of the image artifacts in a 4-slice helical computed tomography have been discussed as follows: (1) changeover in pairs of data used in z interpolation, (2) sampling interval in z, and (3) the cone angle. This study analyzes the first two causes of the artifact and describes how the current algorithm [K. Taguchi and H. Aradate, Radiology 205P, 390 (1997); 205P, 618 (1997); Med. Phys. 25, 550–561 (1998); H. Hu, ibid. 26, 5–18 (1999); S. Schaller et al., IEEE Trans. Med. Imaging 19, 822–834 (2000); K. Taguchi, Ph.D. thesis, University of Tsukuba, 2002] solves the problem. An interpolated sinogram for a slice at the edge of a ball phantom shows discontinuity caused by the changeover. If we extend the streak artifact in the reconstructed image, it crosses the focus orbit at the corresponding projection angle. Applying z filtering can reduce such causes by its feathering effect and mixing data obtained by different cone angles; the best results are provided when z filtering is applied to densely sampled helical data.